INSEPARABLE PARTS OF SUSTAINABILITY: BUSINESS, CLIMATE CHANGE, AND INTEGRATED REPORTING - Caliskan, Arzu Ozsozgun; Esen, Emel (EMERALD GROUP PUBLISHING LTD, 2017)
Purpose - Climate change is one of the most major risks facing today's companies. Evaluating the climate change risks and opportunities which are related to a company's operations is important for both the companies and their stakeholders' sustainability, as a whole. Thereby, from theoretical perspectives, the primary objective of the chapter is to illustrate the role of integrated reporting for business in climate change and the management of the risks and opportunities associated with climate change. Design/methodology/approach - An extensive literature research is conducted in order to understand the relationship between integrated reporting and business role in climate change and also the role of reports in managing the risks and opportunities associated with climate change. Findings - A company that successfully addresses the way in which it affects and is affected by climate change could manage its risk properly and also provide a positive contribution to the creation of more sustainable world and governments' climate change goals. Research limitations/implications - The research is a theoretical study; for further studies, empirical studies can be conducted to understand the role of integrated reporting to manage the risks and opportunities associated with climate change. Practical implications - This study may be useful for managers and governmental agencies in realizing the role between integrated reporting and its contribution to being a sustainable firm and in managing effects of climate change. Originality/value - There is lack of studies that analyze the role of integrated reporting and the managing of risks and opportunities associated with the climate change. Examining the issue will add value to the literature in this area.
Keywords: Sustainability; climate change; risk management; integrated reporting; corporate reporting; Environmental Sciences & Ecology; Business & Economics